Effects of Salinity Stress on Grasspea (Lathyrus sativus L.) and Its Wild Relatives: Morpho-Physiological Insights at the Seedling Stage - Khawla Aloui; Outmane Bouhlal; Hasnae Choukri; Priyanka Gupta; Keltoum El Bouhmadi; Noureddine El Haddad; Khadija El Bargui; Fouad Maalouf; Shiv Kumar (Plants)
Salinity is a critical abiotic stress influencing plant growth. However, its effect on grasspea (Lathyrus sativus L.) remains insufficiently explored. The present study screened 24 germplasm accessions representing 11 Lathyrus species at the seedling stage at 0, 100, and 150 mM NaCl concentrations using a hydroponic system. Our findings indicated that salt stress had a significant effect on all assessed traits, including a reduction in relative leaf water content and SPAD index, a decline in the length and biomass of shoots and roots, and an elevation in their corresponding dry contents. The grasspea accessions displayed a wide range of responses to salt stress. This variation allowed the identification of nine tolerant accessions at both stress levels, belonging to cultivated and wild relative species, specifically LAT 495, IG 65117, L.OCH, IG 65273, IG 64931, IG 114526, IG 64892, IG 66065, and IG 65018. Four accessions, namely IG 110632, IG 114531, IG 65133, and IG 66026, demonstrated tolerance only at 100 mM NaCl concentration. Through identifying these promising accessions, our research offers crucial insights for the initial screening of tolerant genotypes in grasspea, setting the stage for further studies to decipher the intricate mechanisms of salinity tolerance in these accessions.